2017
DOI: 10.1002/anie.201710186
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Thiocarbonyl Fluoride Generated from Difluorocarbene with Amines

Abstract: The reaction of thiocarbonyl fluoride, generated from difluorocarbene, with various amines under mild conditions is described. Secondary amines, primary amines, and o-phenylenediamines are converted to thiocarbamoyl fluorides, isothiocyanates, and difluoromethylthiolated heterocycles, respectively. Thiocarbamoyl fluorides were further transformed into trifluoromethylated amines by using a one-pot process. Thiocarbonyl fluoride is generated in situ and is rapidly fully converted in one pot under mild conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 78 publications
1
59
0
Order By: Relevance
“…150 Classical and routinely used methods to prepare difluoromethylthioethers employ appropriate thiolates and "CF 2 " species, [151][152][153] which is in most cases difluorocarbene (Scheme 28a, left). [154][155][156][157][158][159][160][161][162][163][164][165][166] These early methods suffer from a limited substrate scope and low step economy due to the harsh conditions and stepwise assembly of the -SCF 2 H moiety. In light of these issues, the Goo en group took a step forward to extend the scope by employing the Langlosis β type nucleophilic displacement of thiocyanates (-SCN) by TMSCF 2 H (Scheme 28a, right).…”
Section: Photo-induced C Sp2 -H Difluoromethylthiolation: Synthesis Omentioning
confidence: 99%
“…150 Classical and routinely used methods to prepare difluoromethylthioethers employ appropriate thiolates and "CF 2 " species, [151][152][153] which is in most cases difluorocarbene (Scheme 28a, left). [154][155][156][157][158][159][160][161][162][163][164][165][166] These early methods suffer from a limited substrate scope and low step economy due to the harsh conditions and stepwise assembly of the -SCF 2 H moiety. In light of these issues, the Goo en group took a step forward to extend the scope by employing the Langlosis β type nucleophilic displacement of thiocyanates (-SCN) by TMSCF 2 H (Scheme 28a, right).…”
Section: Photo-induced C Sp2 -H Difluoromethylthiolation: Synthesis Omentioning
confidence: 99%
“…The imidazole NH group was able to act as an ucleophilic site to form abridged ring (C25). Increasing the scale of the reaction to 10 mmol still afforded the desired product C25 in good yield (70 %), which demonstrates the synthetic utility of this tandem strategy.A lthough the heterocyclic NH group is ap otential reactive site for difluoromethylation with difluorocarbene, [2d] the NH moieties in the above products remained intact, enabling further transformations.T he structures of products C6 [14] and C23 [15] were confirmed by using Xray diffraction (see the Supporting Information).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In continuation of our research interest in the chemistry of R F X (R F  = fluoroalkyl group; X = heteroatom) installation (Yu et al., 2017, Zheng et al., 2015, Zheng et al., 2017), we have now investigated the trifluoromethoxylation of alcohols. We found that the Ph 3 P/ICH 2 CH 2 I system could effectively activate the hydroxyl group to achieve dehydroxytrifluoromethoxylation of alcohols with the CF 3 O − anion.…”
Section: Introductionmentioning
confidence: 99%